2011
DOI: 10.4161/viru.2.4.16137
|View full text |Cite
|
Sign up to set email alerts
|

A 60-day probiotic protocol withDietziasubsp.C79793-74prevents development of Johne's disease parameters after in utero and/or neonatalMAPinfection

Abstract: The research reported herein was designed to assess whether the bacterium, Dietzia subspecies C79793-74, used as a probiotic, could prevent development of parameters indicative of bovine paratuberculosis after potential in utero, birthing and neonatal (colostrum) exposure to Mycobacterium avium subspecies paratuberculosis (MAP). Such exposure avenues are especially relevant for dairy farms practicing good management procedures since calves on these farms could be infected via dams that have yet to be identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…Symptomatic or end-stage Johne cattle on the other hand must continue Dietzia treatments for their lifetime and will benefit from short treatment intervals with the glucocorticoid dexamethasone. 27,28 These findings are particularly interesting due to the fact that no adverse side effects were reported in cows receiving prolonged Dietzia treatments for up to three years. Most recent findings by Click et al have reported that it is the continued administration of a live viable bolus of Dietzia that is the causative agent of diminished MAP-associated disease parameters.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Symptomatic or end-stage Johne cattle on the other hand must continue Dietzia treatments for their lifetime and will benefit from short treatment intervals with the glucocorticoid dexamethasone. 27,28 These findings are particularly interesting due to the fact that no adverse side effects were reported in cows receiving prolonged Dietzia treatments for up to three years. Most recent findings by Click et al have reported that it is the continued administration of a live viable bolus of Dietzia that is the causative agent of diminished MAP-associated disease parameters.…”
mentioning
confidence: 74%
“…17,18,23 Reports of variability in the sensitivity of the ELISA for the diagnosis of MAP-positive sera for isolates derived from different host species is not surprising since antigen preparation is not standardized. [24][25][26] Although the current challenges discussed here have been plaguing Johne disease researchers for some time, recent events in research conducted by Click et al [26][27][28][29] shed a sense of optimism on a somewhat overwhelming subject. 29 This data shows a direct impact of Dietzia not only on the shedding of MAP bacteria in the feces but also on the disease status of the individual.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By using an evolutionarily more 'adept and inert' member of the same family to replace its 'cousin', we could be utilizing a naturally occurring method in evolutionary competition. Data for this potential therapy are based on its effectiveness as a prophylactic therapy in cattle [15]. Dietzia is a nonpathogenic micro organism used to competitively displace and inhibit MAP infection.…”
Section: • • Competitively Inhibiting Mapmentioning
confidence: 99%
“…C79793-74, when used as a probiotic had prophylactic and therapeutic benefits for Johne’s disease [1115], a symptomatic IBD of cattle [1619]. The primary goal of the present report is to outline how/why prophylactic benefits obtained with this bacterium could similarly curtail diarrhea of and/or cure human IBDs, with an emphasis on Crohn’s disease.…”
Section: Introductionmentioning
confidence: 99%